Balancing the Loudness in Speech Processors and Contralateral Hearing Aids in Users of Unilateral Cochlear Implants - Magalhães,Ana Tereza Matos (2021)
Abstract Introduction The use of cochlear implants and hearing aids (bimodal) has been growing with the expansion of the indication for them, and it is important to ensure protocols so that there is a balance of the loudness regarding the two devices. Objective To evaluate if the limited complex sounds present in the frequency bands of the current devices enable the balance of the loudness in adult users of bimodal stimulation, and to analyze if speech recognition improves after balancing. Methods A prospective cross-sectional study with convenience sampling. The sample was composed of 25 adults who had used either a cochlear implant for at least 6 months or a contralateral hearing aid, with a mean age of 46 years. The balancing of the loudness was performed in an acoustic room with the computer's sound box (0° azimuth at 70 dB SPL). The instrumental sounds were filtered through eight different frequency bands. The patients used both hearing devices and were asked if the sound was perceived to be louder in one of the ears or centrally. The speech test was evaluated with sentence silence (65 dB SPL) and/or noise signal ratio of 0 dB/+ 10 dB in free field at 0° azimuth, before and after balancing. Results: Out of the 25 patients, 5 failed to achieve balance at every tested frequency, and 3 achieved balance at almost every frequency, except 8 kHz. There was a significant difference between the speech recognition test only in silence before and after balancing. Conclusion: Most patients achieved sound equalization at all evaluated frequencies under the complex-sound protocol. Additionally, most patients experienced improved speech recognition after balancing.